THE NETFLIX MACHINE: HOW EUROPEAN SCREEN WORKERS INTERPRET AND INTERACT WITH STREAMING DATA - Rasmussen, Nina Vindum (AoIR Selected Papers of Internet Research, 2023)
What does the rise of algorithms and data analytics mean for European screen production? This paper examines the experiences of screenwriters, producers, and directors who have collaborated with data-driven streamers like Netflix and Amazon. The findings arise from on an exploration of the following research questions: (1) How do screen workers engage with broader debates about the impact of data-driven streamers (e.g. Netflix and Amazon) on the European screen industry? (2) How do screen workers make sense of their labour conditions and creativity in a streaming era? (3) How do screen workers evaluate the look, feel, and quality of the resulting streaming output? To answer these questions, I mix concepts and methods from media industry studies, production studies, critical data studies, and critical algorithm studies. The project takes the form of a production study that examines how screen workers negotiate the production dynamics in a streaming era. More specifically, I have interviewed 33 screen workers and carried out what Sherry Ortner (2010) calls an ‘interface ethnography.’ My findings especially focus on the multiple barriers to access – for me as a researcher as well as for the interviewed screen workers. It is well established that streamers like Netflix and Amazon hold audience figures and insights close to their chest. This paper demonstrates some of the ways screen workers interpret and interact with data despite this secrecy. Drilling down into these experiences will illuminate how screen workers make sense of their labour conditions and content output in a streaming era.